RESULTS OF OFF-PUMP MYOCARDIAL REVASCULARIZATION IN HIGH-RISK PATIENTS WITH EUROSCORE>5 - I. M. Sharipov; R. R. Yarbekov; A. A. Ismatov; M. M. Muradov; S. KH. Omonov; T. Z. Vakhidov (Евразийский Кардиологический Журнал)
With the wide spread in the last two decades of the technology of performing myocardial revascularization off-pump, acquires a great scientific and practical significance a question of expanding indications to these operations on patients of high surgical risk group. Aim. To carry out comparative analysis of results of off-pump coronary artery bypass grafting surgery in patients with high and low surgical risks.